Evaluation of the Planet constellation’s daily coverage for estimating the number of vessels at Daikoku Pier automobile terminals, Port of Yokohama, Japan - Murata, Hiroki; Imura, Naoto; Nishinari, Katsuhiro (Frontiers in Remote Sensing, 2024)
The automotive industry is a key industry in Japan; however, the worker shortage has affected transportation in the ports and harbors, including that of automobile shipping. Automobiles are shipped using roll-on/roll-off (Ro-Ro) ships. When many Ro-Ro ships dock at the same time, problems related to the shortage of workers and limited storage space for automobiles are exacerbated, decreasing transportation efficiency. The spatial resolution and temporal frequency of satellite imagery have improved with Planet Labs satellite constellations making daily observations of the Earth’s surface. Moreover, the field of remote sensing is seeing an increasing number of logistic applications. As such, this study aimed to evaluate the Planet constellation’s daily coverage for estimating the actual usage of seaport automobile terminals by counting the number of vessels in each image. Here, we focused on Daikoku Pier automobile terminals in the Port of Yokohama, Japan, from 2018 to 2023. Images were classified by visual interpretation into three categories: data available for analysis, data not available for analysis due to cloud, and lack of data. Over the 6-year period, 37.1% of the data were classified as data available for analysis; 21.2%, data not available for analysis due to cloud; and 41.8%, lack of data. The visual inspection survey was conducted twice, with an agreement rate of 90.5% between the two surveys. The number of vessels were then counted two times from “data available for analysis” class, and the discrepancies were corrected. This result was compared to the actual schedule information and the accuracy was 89.0%. The number of vessels docked at the same time tended to be lower in August than in other months. The days from the 25th to 31st tended to have a higher number of vessels than other days, regardless of the month. It seems difficult to use Planet constellation for daily site progress management because data was sometimes available 1 day per month. Planet constellation can be useful in estimating the actual usage through long-term monitoring. We expect that the results of this study will be helpful to those interested in using daily satellite imagery for improving work conditions and efficiencies.